Pengujian Validitas dan Reliabilitas Skala Employee Well-being Dosen di Perguruan Tinggi - Sunarsih Sunarsih; Habibullah Habibullah; Alfina Tiurmida Sitanggang; Arifin Arifin; Putri Fatimah (Journal on Education, 2024)
This study investigates the validity and reliability of the Employee Well-Being Scale tailored for university lecturers. The scale was designed to measure the multi-dimensional aspects of well-being among academic staff. Participants included 123 full-time lecturers from various universities across Indonesia, selected through random sampling to represent diverse academic environments. Inclusion criteria required lecturers to have a minimum of two years of teaching experience and active involvement in academic activities such as teaching, research, and administrative duties. The instrument was administered via an online survey to maximize efficiency and participation. Data analysis employed Confirmatory Factor Analysis (CFA) using SPSS software. The Kaiser-Meyer-Olkin (KMO) measure confirmed sample adequacy with a value exceeding 0.5. The Anti-Image Matrix revealed sufficient Measures of Sampling Adequacy (MSA) values (>0.5) for individual variables. Total Variance Explained analysis identified the percentage of variance accounted for by extracted factors, while the Scree Plot helped determine the number of significant factors. The Rotated Component Matrix ensured that items strongly loaded onto their respective factors. Reliability testing yielded a Cronbach’s Alpha value of 0.948, indicating high internal consistency. The results validate the Employee Well-Being Scale as a reliable tool for assessing well-being among university lecturers, offering robust psychometric properties for further academic and practical applications. This study contributes to the development of evidence-based measures for promoting employee well-being in the higher education sector.